2002
DOI: 10.1002/1521-4095(20020318)14:6<452::aid-adma452>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes Prepared by Spinning and Carbonizing Fine Core-Shell Polymer Microspheres

Abstract: Carbon nanotubes prepared from core–shell polymer particles are reported. As depicted in the Figure, polymethylmethacrylate (PMMA) core/polyacrylonitrile (PAN) shell microspheres are blended with a PMMA matrix, spun, and elongated. Then the shell is stabilized and finally carbonized to produce contaminant‐free carbon nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…It should be emphasized that it is possible to synthesize the core/shell PMMA/PAN composite latex particles with an almost smooth surface by decreasing the amount of the second-stage AN monomer relative to the PMMA seed polymer. These particles were employed to prepare carbon nanotubes by a polymer blend technique [20]. On the other hand, we also carried out the second-stage polymerization using a water-soluble non-ionic azo-initiator, 2,2 0 -azobis[2-methyl-N-(2-hydroxyethyl)propionamide] (VA-086).…”
mentioning
confidence: 99%
“…It should be emphasized that it is possible to synthesize the core/shell PMMA/PAN composite latex particles with an almost smooth surface by decreasing the amount of the second-stage AN monomer relative to the PMMA seed polymer. These particles were employed to prepare carbon nanotubes by a polymer blend technique [20]. On the other hand, we also carried out the second-stage polymerization using a water-soluble non-ionic azo-initiator, 2,2 0 -azobis[2-methyl-N-(2-hydroxyethyl)propionamide] (VA-086).…”
mentioning
confidence: 99%
“…Oya et al reported that carbon nanotubes could be prepared by spinning and carbonizing core-shell polymer particles, which were composed of polyacrylonitrile (PAN) as carbon precursors and polymethylmethacrylate (PMMA) as a thermally decomposable polymer (2). We directed our attention to the potentialities of polymer materials for processing, and supposed we could deriver the desired shapes and controlled structures of carbon nanoproducts when we could prepare the polymer precursors controlled in nanoscale.…”
Section: Carbon Nanoparticles Made From Pan-based Precursorsmentioning
confidence: 99%
“…Table 2 shows that the equilibrium morphology of PMMA/PAN composite particles synthesized by soapless batch-seeded emulsion polymerization should be core-shell structure, which has the minimum interfacial free energy change, which is verified by the result of Hulicova. [8] For the sake of simplification, the effects of initiator type or cross-linking are not considered in the calculation of Table 2. According to the study of Chen, [17] the type of initiator can change the interfacial tension between polymer and water interface, which further changes the morphology of composite particles.…”
Section: The Equilibrium Morphology Of Composite Particlesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Depending on the thermodynamic and kinetic polymerization parameters, as well as the polymerization mechanism, the morphology of composite particles varies from core-shell, hemisphere, snowman, sandwich, raspberry-like to inverted core-shell. The morphology of composite particles can sensitively change the macroscopic properties of materials over a wide range.…”
Section: Introductionmentioning
confidence: 99%